The Role of Financial Planning on Farmers Productivity and Well Being in Sarawak - Azra, Tilai (Universiti Malaysia Sarawak, 2022)
This study emphasizes on a new phenomenon that has been gaining attention in recent years, namely the productivity and wellbeing of farmers in Malaysia. Inadequate emphasis on these farmers, despite the importance of Bario Rice as a Geographical Indication for Malaysia, is the main motivation for this study. Consequently, undesirable production may affect the farmer’s wellbeing. Modernization aided by the government has yet to offer a profound outcome for the paddy cultivation and farmer’s wellbeing. Interestingly, the link between productivity and wellbeing can be moderated by financial planning. However, there is theoretical disagreement between agentic work behaviour and the eudaimonic per-spective. The proponents of agentic work behaviour found that productivity leads to better wellbeing. Conversely, the proponents of eudaimonic perspective argue that wellbeing leads to better productivity. This no consensus situation might be due to the absence of moderation. Thus, this research offers financial planning as moderation in the issue of productivity and wellbeing for the farmers. A face to face interviews were carried out with 115 farmers who were solely or jointly responsible for Bario rice farm productivity. The OLS regression was conducted along with instrumented regression to eliminate the reverse causality effect. The results show that wellbeing improves as productivity and financial planning becomes better. Farmers are less likely to achieve happiness as health condition deteriorates. The moderating role of financial planning on the relationship between produc-tivity and wellbeing is not statistically significant. This research would enrich the under-standing of the theories that are applied in this research which is the Life Cycle Hypothesis Theory, the Theory of Wellbeing and the Agentic Work Behaviour Theory. From this study, policymakers could understand the status or livelihood of paddy farmers and im-plement sound actions that would fit the current situation in the Bario highland. This re-search, by all means, lays the foundations for any further research in this topic with more focus on other characteristic dimensions such as Gayo Coffee, Bintangor Tree and other types of farming.